2008
DOI: 10.1074/jbc.m709273200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Superoxide Dismutase Inhibits Inflammation by Preventing Oxidative Fragmentation of Hyaluronan

Abstract: Extracellular superoxide dismutase (EC-SOD) is expressed at high levels in lungs. EC-SOD has a polycationic matrix-binding domain that binds to polyanionic constituents in the matrix. Previous studies indicate that EC-SOD protects the lung in both bleomycin-and asbestos-induced models of pulmonary fibrosis. Although the mechanism of EC-SOD protection is not fully understood, these studies indicate that EC-SOD plays an important role in regulating inflammatory responses to pulmonary injury. Hyaluronan is a poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
133
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 72 publications
(49 reference statements)
6
133
0
1
Order By: Relevance
“…Lung inflammation was significantly decreased by SOD3 overexpression in mice exposed to CS and elastase. This is in agreement with previous studies showing a protective effect of SOD3 on lung inflammatory responses to hyperoxia, bleomycin, and asbestos (4,17,29,30). Furthermore, the SOD mimetic exhibited a protective effect in lung inflammation in SOD3 KO as well as in WT mice.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Lung inflammation was significantly decreased by SOD3 overexpression in mice exposed to CS and elastase. This is in agreement with previous studies showing a protective effect of SOD3 on lung inflammatory responses to hyperoxia, bleomycin, and asbestos (4,17,29,30). Furthermore, the SOD mimetic exhibited a protective effect in lung inflammation in SOD3 KO as well as in WT mice.…”
Section: Discussionsupporting
confidence: 82%
“…Con, control; Mimetic, SOD mimetic. flammatory response caused by a variety of stimuli (15)(16)(17)(18)(23)(24)(25). Hence, immunoblotting was performed to determine whether the protective effect of SOD3 on lung inflammation and subsequent emphysema is caused by an increased integrity of ECM in mouse lung exposed to CS.…”
Section: Sod3 Protected Against Cs-induced Heparan Sulfate Shedding Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular superoxide dismutase or superoxide dismutase 3, the last discovered superoxide dismutase isoform that binds lung matrix components, inhibiting their fragmentation in response to oxidative stress, [38][39][40] is the primary extracellular lung antioxidant enzyme. 41,42 It protects the extracellular matrix during lung injury [43][44][45][46] and accounts for the majority of superoxide dismutase activity in airways and vessels.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 One mechanism by which EC-SOD inhibits inflammation is directly binding to and inhibiting oxidative fragmentation of several components in the extracellular matrix including collagen, heparan sulfate, and hyaluronan after interstitial lung injury. 11,[21][22][23][24] The importance of endogenous pulmonary EC-SOD was recently highlighted in a study that demonstrated that acute loss of EC-SOD resulted in 85% mortality secondary to the spontaneous development of acute respiratory distress syndrome. 25 This indicates that EC-SOD is essential for protecting the lungs against inflammation and injury even in ambient air.…”
mentioning
confidence: 99%